2008
DOI: 10.2355/isijinternational.48.320
|View full text |Cite
|
Sign up to set email alerts
|

Solidification Behavior of AZ31 Magnesium Alloys Using an Electromagnetic Vibration Technique

Abstract: The commercial magnesium-based AZ31 alloy was solidified in a static magnetic field when an alternating electric current, perpendicular to the direction of the magnetic field, passes through the alloy. In this case, the periodical Lorentz force is generated, making the conductor vibrate centering on the initial equilibrium position. In this paper, we investigated the microstructure evolution of the alloy as a function of vibration frequency, magnetic flux density and electric current, respectively. The solidif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…[24][25][26][27] In the present study, when the alternating current was applied into the hypereutectic Mg-Si melt at high temperatures of 770 C and 740 C, it was interesting that obvious agglomerations of refined Mg 2 Si crystals occurred in these two samples and the Mg 2 Si crystals distributed non-uniformly, as shown in Figs. 7(a) and 7(b).…”
Section: Microstructural Evolution Of Hypereutectic Mg-simentioning
confidence: 85%
See 2 more Smart Citations
“…[24][25][26][27] In the present study, when the alternating current was applied into the hypereutectic Mg-Si melt at high temperatures of 770 C and 740 C, it was interesting that obvious agglomerations of refined Mg 2 Si crystals occurred in these two samples and the Mg 2 Si crystals distributed non-uniformly, as shown in Figs. 7(a) and 7(b).…”
Section: Microstructural Evolution Of Hypereutectic Mg-simentioning
confidence: 85%
“…Therefore, no obvious agglomerations of the Mg 2 Si crystals were found in the samples treated by application alternating current from starting temperatures of 700 and 670 C. Usually, it is widely accepted that the refinement of the structures caused by EMV attributes to the fragmentation by mechanical stress and by the re-melting of the primary solid phase due to constitutional undercooling. 26,27) For the latter, it is not necessary to think of the bonding among atoms. For the former, the present authors think that the dendritic Mg 2 Si crystals were fragmented from some weak parts subjected to the EMV.…”
Section: Microstructural Evolution Of Hypereutectic Mg-simentioning
confidence: 99%
See 1 more Smart Citation
“…The refining effect could be obtained only when EMV was imposed in the initial stage of the solidification. More recently, Li et al 27) reported that the effects of the operating parameters of EMV on the solidification behavior of AZ31 alloy and the best refining efficiency could be obtained under the condition of the optimum operating parameters.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] In particular, it has long been established that the electromagnetic vibration (EMV) can effectively refine the microstructures for a large range of metals prepared by the ingot metallurgy process. [20][21][22][23][24][25][26][27][28] For this route, the operating parameters of EMV were proved to be very important to determine the refining efficiency, including vibrating frequency, 22,23,[25][26][27] current density, 24,26,27) magnetic flux density, 26,27) imposition timing, etc. 24,28) For example, Mizutani et al 22) found that the vibration frequency near 1 kHz was most effective for the refinement of the primary silicon in the Al-17 mass%Si treated by EMV.…”
Section: Introductionmentioning
confidence: 99%